Gamma Radiation Synthesis of Cadmium Sulfide Nanoparticles - Vaziri, Parisa (2010)
Semiconductor Cadmium Sulfide nanocomposites capped with polyvinyl alcohol were synthesized using60Co gamma irradiation method as a reducing agent at different concentrations of cadmium and sulfur sources (1:1, 1.5:1.5, 2:2) and different doses of gamma radiation (0, 30, 60, 90, 120 KGy) at room temperature. When the solution was irradiated with γ-rays, the radiolysis of water produces many active species such as solvated electrons and they can reduce S2- ions from the sulphur source step by step which reacted with Cd2+ to generate CdS. The Formation of CdS nanoparticles can be primarily identified from the color change in the as prepared products and confirmed using X-ray powder diffraction. The optical properties of CdS nanoparticles were measured by UV- visible spectrophotometer and found that the absorbance for 1:1 concentration is at 426 nm at 30kGy, 425 nm at 60 kGy, 424nm at 90 kGy and 422 nm at 120 kGy radiation doses. The bandgap energy of CdS nanoparticles were calculated using Tauc formula.When the radiation dose increases from 30 to 120 kGy, the band gap energy increases from 2.64 to 2.71 eV for 1:1, from 2.56 to 2.64 eV for 1.5:1.5 and from 2.54 to 2.58 eV for 2:2 concentrations. The crystalline of nanoparticles were studied using XRD instrument, and found to be cubic CdS with lattice constant of a=5.8304 A°. An increase of the radiation dose improved the crystallization of CdS nanoparticles. The crystalline size of particles was estimated from the diffraction peak using Scherrer‟s equation and the size ofCdS nanocomposites exponentially decreased with the increase of the radiation dose and can be fitted with the expression of the form: